2021
DOI: 10.1177/13506501211058239
|View full text |Cite
|
Sign up to set email alerts
|

Combination of musculoskeletal and wear models to investigate the effect of daily living activities on wear of hip prostheses

Abstract: Numerical wear predictions are gaining increasing interest in many engineering applications, as they allow to simulate complex operative conditions not easily replicable in the laboratory. As far as hip prostheses are concerned, most of the wear models in the literature are based on the simulation of gait (recommended also in experimental wear tests), since gait is considered the most frequent and important motor task to recover after arthroplasty. However, since joint prostheses have been increasingly implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Conversely to the HCF, which were directly measured in vivo thanks to the development of instrumented implants 35 , to date, the trajectory of the hip contact point during daily activities can be only computed by using musculoskeletal models. In this regard, looking at the contact location computed in this study for the stance phase, an arc path located apically in the anterolateral region of the head was observed, which is qualitatively in agreement with the literature 34 , 57 , 58 . Also, it was observed that different offsets led to similar contact trajectories, according to findings reported by De Pieri et al 56 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely to the HCF, which were directly measured in vivo thanks to the development of instrumented implants 35 , to date, the trajectory of the hip contact point during daily activities can be only computed by using musculoskeletal models. In this regard, looking at the contact location computed in this study for the stance phase, an arc path located apically in the anterolateral region of the head was observed, which is qualitatively in agreement with the literature 34 , 57 , 58 . Also, it was observed that different offsets led to similar contact trajectories, according to findings reported by De Pieri et al 56 .…”
Section: Discussionsupporting
confidence: 91%
“…, ISO, ASTM) or experimental studies based on instrumented prostheses. In the first case, it has been shown that standards may underestimate or simplify in vivo loads 34 , 35 . In the second case, researchers are compelled to use the application points reported in the studies, such as the center of the femoral head.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the computational modelling was shown in parametric analyses for the design parameters of the hip [667] and the loading/motion in the knee [668]. Further applications of the computational modelling were made to investigate the effect of different daily activities of the hip [669] and wear of the lateral and medial compartments in the knee [670]. A wear model with the consideration of lubrication was developed in Ref.…”
Section: Natural Synovial Joints and Artificial Joint Replacementsmentioning
confidence: 99%
“…Indeed, JRFs can provide valuable insights into movement disorders such as cerebral palsy (Steele et al, 2012) or into degenerative articular diseases such as osteoarthritis (Kumar et al, 2013). They are also important to define the loading conditions for preclinical experimental tests on artificial joints (Affatato and Ruggiero, 2019;Bergmann et al, 2016;Heller et al, 2005), or they could serve as an input to finite-element models aimed at evaluating wear processes in joint implants (Lin et al, 2018;Mattei et al, 2021;Ruggiero et al, 2018) or at predicting bone adaptations (Geraldes and Phillips, 2010).…”
Section: Introductionmentioning
confidence: 99%